Executive Function Evaluation in a Population of Children and Adolescents with Hearing Loss in Bogotá, Colombia. - Ramírez-Guerrero, Sofía; Gómez-Barrera, Daniela; Monsalve-García, Isabella; Bueno-Santamaría, Daniel Felipe; Pradilla, Iván; Vélez-Van-Meerbeke, Alberto; Talero-Gutiérrez, Claudia (Salud Mental)
Introduction: Hearing loss, regardless of the degree or etiology, delays language acquisition and communication skills and consequently executive function development. Objective: The aim of this study is to measure executive function performance in a population of children and adolescents with hearing loss in Bogotá, Colombia. Method: TA cross-sectional observational study was conducted with participants between 5 and 16 years old with prelingual hearing loss and no previous diagnosis of intellectual disability. Six subtests were selected from the Child Neuropsychological Scale to evaluate performance in the following domains: planning and organizing, visual memory, non-semantic graphic fluency, cognitive flexibility, and attention. Results: Overall, percentile mean scores for the total population were average or above average for all subtests. Subjects scored lowest in visual memory domains, including both encoding and recall skills and highest in attention and non-semantic graphic fluency subtests. No significant associations were observed between independent variables (age at diagnosis, chronological age, degree of HL, type of hearing aid, and sex) and subtests scores. Discussion and conclusion: Although hearing loss can delay executive function development, our sample of Colombian children and adolescents with hearing loss receiving multidisciplinary therapy reported similar executive function performance to their normal hearing peers.